Congenital anophthalmia and microphthalmia: epidemiology and orbitofacial rehabilitation - Llorente-González S (Dove Medical Press, 2011)
Sara Llorente-González1, J Peralta-Calvo2, JM Abelairas-Gómez21Ophthalmology Service of Hospital de Torrejón, Madrid, Spain; 2Ophthalmology Service of Hospital Universitario La Paz, Madrid, SpainObjective: To describe the prevalence of congenital anophthalmia and microphthalmia in Hospital Universitario La Paz, and to identify associated risk factors and evaluate cosmetic results in treated and nontreated patients.Methods: A retrospective, descriptive, cross-sectional study of patients treated with orbital expanding techniques (cases) and nontreated patients (controls) was carried out as a comparative case series study. A total of 36 patients with unilateral or bilateral anophthalmia or microphthalmia as main diagnosis were included; 52 epidemiological and management variables for each patient were analyzed. The study evaluated orbital growth and facial symmetry.Results: The overall cosmetic result in the study’s group of patients was satisfactory: 66.7% showed good or very good orbital growth, and 75% showed good or very good facial symmetry. Controls had better cosmetic outcome but showed more cataracts (P = 0.05), inferior colobomas (P = 0.026), and family history (P = 0.056) than the cases. Controls also showed significantly better orbital growth (P = 0.042) and facial symmetry (P = 0.014) than the cases.Conclusion: This study suggests that the mere presence of a globe (controls) still provides better orbitofacial development than the artificial stimulation (cases) currently available for patients with congenital anophthalmia and microphthalmia, who receive internal and external orbital rehabilitation.Keywords: cosmetic outcome, orbital rehabilitation, ocular malformation, congenital cataract, persistent fetal vasculature